Między rajem a piekłem. Obraz dzieciństwa w twórczości Aleksandra Kuprina - Bielniak, Nel (Rusycystyczne Studia Literaturoznawcze, 2016)
This article is devoted to reflections on the functioning of the myth of childhood in Aleksandr Kuprin’s works. By creating the images of his juvenile characters, the writer often refers to the aesthetical-axiological canons taken from the Christian tradition and their iconographical realisations addressing child-angel associations. However, he frequently re-evaluates the existing schemes, showing that the social situation of a child, his or her upbringing, or the system of values ordering his or her family life may negate the Arcadian vision of childhood. That is why child characters in Kuprin’s works exist between two poles: carelessness and torment, love and rejection, idyll and tragedy, innocence and misdeed.